Una especie nueva de Opuntia del estado de Querétaro - Sanchez M., Emiliano; Villaseñor, Jose Luis (Instituto de Ecología, A.C., 1994)
A new species of Cactaceae, Opuntia elizondoana, from the state of Querétaro, is described and illustrated. Its affinities with O. decumbens and O. puberula are discussed, as well as data about their distribution, habitat and morphological characters distinguishing them are provided.